Utilization of Superior New Variety of Rice (VUB) to Increase Farmer Productivity and Income - Irma Susanti; Fuad Nur Azis; mohammad saeri (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Efforts are needed to increase rice production. One of the technology components is superior varieties. Many new high yielding varieties have been produced by IAARD, but not all varieties are adaptive in one location. This study aims to determine the new high yielding varieties that benefit farmers. The assessment was carried out from May to September 2017, in the village of Warujayeng, Tanjunganom District, Kab. Nganjuk. There are 13 new high yielding varieties used, namely: Inpari-4; Inpari-6; Memberamo; Ciherang; Established-P05; Inpari-30 / C-Sub-1; Inpari32; Inpari-33; Inpari-42; Inpari-43; Inpara-2; Inpara-8 and Inpara-9. The results showed that the highest productivity was achieved by Inpari-43 (8.51 t / ha), followed by Inpari-42 (8.13 t / ha), while the lowest yield was Inpara-2 (5.84 t / ha). The highest profit was achieved by the Inpari 43 variety of Rp. 23,121,900, - there was an increase of 65.8% compared to the existing varieties (Ciherang). The highest R / C ratio is Inpari 43 of 2.09. All VUB tested the value of R / C Ratio is> 1, which means efficient.